Porcelain Fear - Greif, Tatjana (Identities: Journal for Politics, Gender and Culture, 2013)
The article is a short consideration about different faces of fear and its abuse for suppressing the society – about the political fear from non-obedient citizens, the fear of citizens from corporative state, the fear of people from other people, and between people. LGBT people are both representing fear to the others and they suffer the phobia of the society. The article is about how in the Balkans a small porcelain figurine can become a threat just with a hint of lesbianism. Author(s): Tatjana Greif Title (English): Porcelain Fear Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 55-57 Page Count: 3 Citation (English): Tatjana Greif, “Porcelain Fear,” Identities: Journal for Politics, Gender and Culture, Vol. 10, No. 1-2 (Summer-Winter 2013): 55-57.